Analysis of auto-fluorescence images for automatic detection of abnormalities in oral cavity - Awais, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Oral Potential Malignant Disease (OPMD) is a growing and significant health problem all over the world. OPMDs have the potential to lead to oral cancer. The detection and diagnosis of these OPMDs in their early phases is a challenging task for clinicians. This paper focuses on the identification of OPMDs in visually enhanced lesion scope (VELscope) images using the contrast stretching technique. The parameters of the contrast stretching technique have been set automatically based on a statistical analysis of a set of images. The results show a better differentiation of OPMDs from the normal region. The proposed technique has shown a higher (greater than 90) accuracy, sensitivity and specificity. Â© 2015 IEEE.